Pyrolysis of Used Tires Using Spent Catalyst of Crude Oil Cracking Process from Pertamina RU III - kiagus ahmad roni; Muhammad Roy Tri Handono; Zahrul Mufrodi (Universitas Ahmad Dahlan, 2020)
The additional waste of used tires increases every year in direct proportion to the growth of motorized vehicles. Problems caused by used tire waste will also increase if there is no right solution to reduce waste. Catalytic pyrolysis is one way to change used tires into another form that has the benefit of liquid fuel. Polystyrene contained in used tires is a synthetic polymer that can be converted into liquid fuel by pyrolysis method. PT Pertamina RU III Palembang's former petroleum cracking catalyst can still be reused as a catalyst in the pyrolysis of used tires to improve the process by reducing cracking temperature and cracking time to obtain maximum liquid fuel. The process is carried out using 500 grams of used tire rubber with catalysts of 0%, 20%, 40%, 60%, and 80% of the weight of used tire rubber with a heating time of 120 minutes and 180 minutes. Based on the results of the study, the highest volume of liquid fuel was produced from the addition of an 80% catalyst from the weight of the used tire rubber with a pyrolysis time of 180 minutes, 71 ml. The liquid fuel obtained is then analyzed using Gas Chromatography. From this analysis, the results obtained from the pyrolysis of used tire rubber using a catalyst used by PT Pertamina RU III Palembang used oil is approaching premium fuel. So it can be concluded that used rubber tires containing polystyrene can be processed into liquid fuels.